2016
DOI: 10.17795/jpr-6276
|View full text |Cite
|
Sign up to set email alerts
|

Add-on Levetiracetam in Children With Refractory Epilepsy: A Systematic Review

Abstract: Context: Recently, new anti-epileptic drugs are marketed to be used as an add-on to the traditional drugs in children with refractory epilepsy. Levetiracetam is a second-generation of new anti-epileptic drugs with unknown precise mechanism of action in brain and synaptic vesicle in children with drug resistant epilepsy. Herein, the efficacy and safety of add-on levetiracetam in children with refractory epilepsy is reviewed.Evidence Acquisition: A literature review was performed on efficacy and safety of add-on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The effectiveness and tolerance of LEV as an adjunct AED was described in a review as 42.24%, among the children ≤ 18 years with intractable epilepsy, reducing the frequencies of seizure beyond 50%, out of which 11.8% had become free of seizure. 28 Some others also noted comparable results. 29,30 In a report presented by Opp et al described that above 50% reduction in seizure was observed in 24.9% of the individuals when treated with LEV.…”
Section: Discussionmentioning
confidence: 73%
“…The effectiveness and tolerance of LEV as an adjunct AED was described in a review as 42.24%, among the children ≤ 18 years with intractable epilepsy, reducing the frequencies of seizure beyond 50%, out of which 11.8% had become free of seizure. 28 Some others also noted comparable results. 29,30 In a report presented by Opp et al described that above 50% reduction in seizure was observed in 24.9% of the individuals when treated with LEV.…”
Section: Discussionmentioning
confidence: 73%
“…Lamotrigine and levetiracetam are effective in either genetic generalized epilepsy or focal epilepsy. Levetiracetam is safer 27,28 and as effective as valproate. Lamotrigine and levetiracetam are among best tolerated AEDs.…”
Section: Broad Spectrum Antiepileptic Drugsmentioning
confidence: 97%